Marsilea: an intuitive generalized paradigm for composable visualizations - Yimin Zheng; Zhihang Zheng; André F. Rendeiro; Edwin Cheung (Genome Biology)
Abstract Biological data visualization is challenged by the growing complexity of datasets. Traditional single-data plots or simple juxtapositions often fail to fully capture dataset intricacies and interrelations. To address this, we introduce “cross-layout,” a novel visualization paradigm that integrates multiple plot types in a cross-like structure, with a central main plot surrounded by secondary plots for enhanced contextualization and interrelation insights. We also introduce “Marsilea,” a Python-based implementation of cross-layout visualizations, available in both programmatic and web-based interfaces to support users of all experience levels. This paradigm and its implementation offer a customizable, intuitive approach to advance biological data visualization.